(untitled) (TEST Antologia di Diritto Pubblico, 2025)
The notion of action within constitutional justice has been developed by procedural theorists as if it were possible to conceive of a subjective legal position abstractly related to the constitutional legitimacy of acts subject to the Constitution, or, alternatively, as if a constitutional process of liberties could be constructed around the category of prejudiciality. The rationale of a system of constitutional justice lies in determining the degree of movement permitted to a rigid constitution: for a constitution that were perfectly rigid would also be entirely immobile, and would therefore require a merely negative, yet pervasively omnipotent, form of review. In the Italian system, the procedural mechanisms of access and the rules governing constitutional adjudication define both the limit and the foundation of constitutional rigidity. A constitutional court that recognises no constraint other than its own prudence risks encroaching upon the sphere of constituent sovereignty. The concept of action, therefore, cannot be understood as the procedural projection of an individual will be safeguarded by the constitutional order through constitutional justice. Rather, the modalities of access represent the techniques through which the constitutional order contains the potentially boundless expansion of constitutional adjudication. In actions of direct challenge, the Constitutional Court assumes a pivotal role as a means of continuous — and dynamic — verification of the proper alignment between the form of government and the form of state, a relationship that the crisis of political representation has brought into sharp relief. The emergence of a contentious democracy thus links incidental proceedings with direct actions, delineating a dynamic in which the demands for political justice — no longer mediated by ideology or manageable through representative institutions — are channelled into the sphere of constitutional justice. Through this process, such demands are synthesised within a framework that performs a function of nomopoiesis — the creation of legal norms through adjudication. It may appear unsettling, even paradoxical, that the constitutional body entrusted with ensuring that the majority principle, as expressed through representative mechanisms, does not transgress the limits inherent in the form of the state, should find itself performing a (vigilant, reluctant, yet conscious) function of substitution. Such a function arguably betrays the Court’s foundational mission, yet also reflects the current condition of constitutional democracy.